Cloud Native Applications with Ballerina - Madushan, Dhanushka (Packt Publishing, 2021)
Learn how to build scalable cloud native applications with the new-generation Ballerina language using expert tips and best practices Key Features Work with code samples based on the Ballerina Swan Lake Beta1 version Explore the in-built networking protocol support in Ballerina to develop secure distributed apps Build a Ballerina app with an automated CI/CD pipeline with observability to simplify maintenance and deployment Book Description The Ballerina programming language was created by WSO2 for the modern needs of developers where cloud native development techniques have become ubiquitous. Ballerina simplifies how programmers develop and deploy cloud native distributed apps and microservices. Cloud Native Applications with Ballerina will guide you through Ballerina essentials, including variables, types, functions, flow control, security, and more. You'll explore networking as an in-built feature in Ballerina, which makes it a first-class language for distributed computing. With this app development book, you'll learn about different networking protocols as well as different architectural patterns that you can use to implement services on the cloud. As you advance, you'll explore multiple design patterns used in microservice architecture and use serverless in Amazon Web Services (AWS) and Microsoft Azure platforms. You will also get to grips with Docker, Kubernetes, and serverless platforms to simplify maintenance and the deployment process. Later, you'll focus on the Ballerina testing framework along with deployment tools and monitoring tools to build fully automated observable cloud applications. By the end of this book, you will have learned how to apply the Ballerina language for building scalable, resilient, secured, and easy-to-maintain cloud native Ballerina projects and applications. What you will learn Understand the concepts and models in cloud native architecture Get to grips with the high-level concepts of building applications with the Ballerina language Use cloud native architectural design patterns to develop cloud native Ballerina applications Discover how to automate, maintain, and observe cloud native Ballerina applications Use a container to deploy and maintain a Ballerina application with Docker and Kubernetes Explore serverless architecture and use Microsoft Azure and the AWS platform to build serverless applications Who this book is for This Ballerina Swan Lake book is for cloud developers, integration developers, and ...